Germany's construction industry: Strong growth followed by stagnation - Martin Gornig; Hendrik Hagedorn (DIW Economic Bulletin, 2012)
2011 was one of the construction industry's strongest years of growth since German reunification. For the year as a whole, a nominal increase in construction volume of almost eight percent is expected. The price increase is forecast at over 2.5 percent. Real construction volume in 2011 will be over five percent higher than in 2010. However, according to current information, we can expect the construction industry to experience a break in growth in 2012. Real construction volumes will barely be higher than in 2011. This development is partly due to the phasing out of economic stimulus packages. Further, the promising announcements of support for energy-efficient modernization as part of the change in energy policy for residential construction has had more of a negative impact on the construction industry. The predicted reluctance to invest will only be overcome if the German government swiftly determines specific financing conditions for the coming years.
Keywords: E32; E66; 330; construction industry forecast; economic outlook